Лaтинскaя Aмерикa во внешней политике Испaнии - Чукубaев, Е.; Амирулы, А. (International relations and international law Journal, 2018)
Author of this article has considered strengthening of integration processes in Latin America and the resumption of the historical ties with Europe, in which, of course, particularly important role the countries of the Iberian peninsula of Spain and Portugal, which have applied and are making every effort to improve cooperation in Latin America and the European Union. Relations of Latin America and Spain at present determined by a number of trends and creates favorable conditions for the revitalization of the Spanish economic interests in the region, including for the penetration of the Spanish capital’s economy in Latin America. This is due to an increase in the pace of economic development in the Latin American region, accompanied by a process of industrialization that gave rise to the need to find new markets and sources of funding. Key words: Latin America, Spain, the EU, integration process.